Revalidating vernacular techniques for a sustainable built environment by way of selected examples in the Eastern Cape - Steenkamp, Colleen Avice (University of the Free State, 2012)
Contemporary design and construction methods often entail large amounts of wastage, high construction costs, high energy consumption for heating and cooling, and thus a large carbon footprint, which limits their sustainability. While South Africa’s granting of much-needed houses to the indigent population is noteworthy, the quality of these houses sometimes leaves much to be desired. In addition, the cultural identity of the inhabitants of these houses is being lost. The purpose of this study is to determine if vernacular architecture and building techniques could be a possible solution to the above-mentioned problems concerning contemporary design in the Eastern Cape. Five case studies were conducted for this research. The first involved a perception analysis – through a questionnaire – of inhabitants of vernacular and contemporary homes in uMasizakhe, Graaff-Reinet. The next two case studies involved documenting the now-demolished Luxolweni community on the outskirts of Hofmeyr and three now-demolished rondavels surrounding Hofmeyr. The last two case studies are of recently-built contemporary designs. The first is a vernacular building in rural Centane and the second is a building steeped in innovations for sustainability in East London. The main results from the study revealed that the material properties of vernacular buildings are in many ways superior to their contemporary counterparts (these houses are cooler in summer and warmer in winter), vernacular homes are considered socio-culturally acceptable by their inhabitants, vernacular techniques can be successfully incorporated into contemporary architecture and that innovations can be incorporated within vernacular architecture for longevity. It was concluded that vernacular architecture has the potential to improve human settlements and the sustainability of the built environment, as well as strengthening the cultural identity of the local populace. This research is relevant in a country where buildings are often unsustainable and housing is lacking, as it offers a potential solution to these problems.

Kontemporêre ontwerp en konstruksie metodes-veroorsaak in baie gevalle groot hoeveelhede vermorsing, hoë konstruksie koste en hoë energie-verbruik vir verhitting en verkoeling. Gevolglik is daar dus _ groot koolstofvoetspoor wat die volhoubaarheid daarvan inperk. In Suid Afrika is die verskaffing van broodnodige huise aan die hulpbehoewende bevolking noemenswaardig. Die gehalte van hierdie huise laat soms veel te wense oor. Voorts gaan die kulturele identiteit van die inwoners verlore. Die doel van hierdie studie is om te bepaal of inheemse argitektuur en boutegnieke as _ oplossing kan dien vir die bogenoemde probleme in kontemporêre ontwerp in die Oos-Kaap. Vyf gevallestudies is gedoen vir die doelwit van hierdie navorsing. Die eerste handel oor `n persepsieanalise –by wyse van _ vraelys- van die inwoners van inheemse en kontemporêre huise in uMasizakhe naby Graaff-Reinet. Die volgende twee gevallestudies behels die dokumentering van die nou afgebreekte Luxolweni gemeenskap aan die buitewyke van Hofmeyr en die nou afgebreekte rondawels rondom Hofmeyr. Die laaste twee gevallestudies behels onlangs geboude kontemporêre ontwerpe. Die eerste is _ inheemse gebou in die landelike Centane en die tweede is _ gebou wat deurspek is van innoverings vir volhoubaarheid in Oos-Londen. Die resultaat van die studie het onthul dat die eienskappe van die materiaal van die inheemse geboue in baie gevalle beter is as die kontemporêre eweknieë daarvan (hierdie huise is koeler in die somer en warmer in die winter). Inheemse huise word beskou as meer aanvaarbaar in sosiokulturele sin deur hulle inwoners, inheemse tegnieke kan suksesvol in kontemporêre argitektuur geïnkorporeer word en innoverings kan in die inheemse argitektuur geïnkorporeer word vir langlewendheid. Daar is tot die slotsom gekom dat inheemse argitektuur die potensiaal het om menslike vestings te verbeter, die volhoubaarheid van die bou omgewing te verbeter asook om die kulturele identiteit van die plaaslike bevolking te versterk. Hierdie navorsing is relevant in ‘n land waar geboue meermale nie volhoubaar is nie en behuising skaars is. Dit bied ‘n potensiële oplossing vir hierdie probleem.
Dissertation (M.Arch. (Architecture))--University of the Free State, 2012
Keywords: Innovation; Knowledge transfer; Indigenous knowledge; Sustainability; Vernacular architecture; Vernacular architecture -- Eastern Cape; Architecture -- South Africa -- Eastern Cape